Sustainable economic development: analysing the relevance of theory and the integration of social, environmental and economic objectives - Paulina Nowakowska (Zarządzanie Innowacyjne w Gospodarce i Biznesie)
The subject of this paper is the management strategy for remote working teams. In an era of globalisation and technological advancement, remote working has become commonplace, presenting organisations with the challenge of managing such teams effectively. At the outset, the paper highlights the role of trust in the management of virtual teams. By building trust, employees are given more autonomy and clear guidelines. Virtual communication is at the forefront of this process, where the use of different communication tools is essential. Another important point is to create a common culture within the virtual team. Holding online meetings, or even occasional face-to-face meetings, can help the team develop a sense of belonging and identification with the organisation. The paper also highlights the importance of continuously improving virtual team management skills, considering new technologies and best practices. In the changing work environment of the 21st century, the effective management of virtual teams is becoming an increasingly essential in the success of an organisation. The cultivation of trust, communication, work-life balance, team culture and the development of leadership skills are all determinants of successful team management.